Correction of vitamin A and zinc in blood syruises of horses at the last trimester for alimentary insufficiency - Шатохін, П. П.; Супруненко, К. В.; Каришева, Л. П.; Деренчук, Ю. І.; Крилевець, Ю. В. (Scientific Progress & Innovations, 2017)
The article presents the results of research on the distribution of A-hypovitaminosis in the mares of the last trimester of pregnancy. For this purpose, the ration of feeding mares was analyzed for the nutrient content. We have established an imbalance with digestible protein, crude fiber, calcium, phosphorus and carotene. According to the results of the clinical examination of the mares, it was founding that of the 17 examined mare 10 goals had symptoms of alimentary hypovitaminosis. The introduction in the last trimester of pregnancy of mares, with signs of hypovitaminosis, orally, of retinol acetate in a dose of 700,000 IU, five times, at intervals of seven days, increases the content of zinc in serum on average by 155 %, and vitamin A in 4,38 times.